An Assessment of Childbearing Preferences in Northern Malawi. Issue 2 (June 2015) - Machiyama, Kazuyo; Baschieri, Angela; Dube, Albert; Crampin, Amelia C.; Glynn, Judith R.; French, Neil; Cleland, John
<x xml:space="preserve">Abstract</x> Fertility preferences are an essential component of family planning program evaluation; however, doubts about their validity in sub‐Saharan Africa exist and little methodological assessment has been carried out. This study investigates prospective fertility intentions in terms of their temporal stability, intensity, degree of spousal agreement, and association with future childbearing in northern Malawi. A total of 5, 222 married women participated in the three‐round study. The odds of having a child or becoming pregnant within 36 months were 4.2 times higher when both wife and husband wanted a child within three years and 2 times higher when both wanted to wait at least three years, compared with the odds when both wanted to cease childbearing. The influence of husbands' and wives' preferences on subsequent fertility was equal. Compared with the intention to stop, the intention to postpone childbearing was less stable, recorded less spousal agreement, and was much less strongly predictive of fertility.